The Role of Islamic Religious Education Teachers in Fostering the Practice of Islamic Teachings Among Students - Aisyah Miftahul Jannah; Ajahari Ajahari; Abdullah Abdullah (STAI Serdang Lubuk Pakam, 2025)
The role of teachers in fostering the practice of Islamic teachings is very important, because it not only teaches religious theory, but also directs students to practice Islamic values in everyday life. This study aims to examine the role of Islamic Religious Education teachers in fostering the practice of Islamic teachings in students at SDN 2 Jingah, North Barito Regency. This research uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that: 1) Islamic Religious Education teachers play an important role in fostering the practice of Islamic teachings with an integrative approach, which includes teaching religious theory, worship practices, and instilling moral values such as honesty and discipline. Teachers guide students to understand and practice Islamic teachings through habituation methods and effective interactive learning. 2) Supporting factors include adequate facilities, a supportive school environment, and parental involvement. However, inhibiting factors such as limited facilities, time, and lack of teacher professionalism were also found.